2018
DOI: 10.1186/s41038-018-0134-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term mental health outcomes after unintentional burns sustained during childhood: a retrospective cohort study

Abstract: BackgroundBurns are a devastating injury that can cause physical and psychological issues. Limited data exist on long-term mental health (MH) after unintentional burns sustained during childhood. This study assessed long-term MH admissions after paediatric burns.MethodsThis retrospective cohort study included all children (< 18 years) hospitalised for a first burn (n = 11,967) in Western Australia, 1980–2012, and a frequency matched uninjured comparison cohort (n = 46,548). Linked hospital, MH and death data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 73 publications
1
15
0
Order By: Relevance
“…In this study it is noted that in 83.9% of participants total body surface area involved in burn injury was up to 25% similar results are seen in study done by Fauerbach 14 , but these results are different from the result of study done by duke et al, that has shown that total body surface area involved in burn injury was up to 25% in 46% of participants 15 . On the contrary there is a study by Vetrichevvel et al, that has noted that in 59% of participants the total body surface area involved after burn was >25% 16 .…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In this study it is noted that in 83.9% of participants total body surface area involved in burn injury was up to 25% similar results are seen in study done by Fauerbach 14 , but these results are different from the result of study done by duke et al, that has shown that total body surface area involved in burn injury was up to 25% in 46% of participants 15 . On the contrary there is a study by Vetrichevvel et al, that has noted that in 59% of participants the total body surface area involved after burn was >25% 16 .…”
Section: Discussionsupporting
confidence: 53%
“…Duke et al, in his study has noted that 32.6% develop anxiety after burn injuries while 27.8% develop depression 15 . Alvi in her study reported that 82% of individuals with burn injuries develop anxiety while 58% individuals with burn injuries develop depression 7 .…”
Section: Discussionmentioning
confidence: 91%
“…Twenty‐two quantitative and 10 qualitative studies were included. Four focused on pediatric burn survivors (Duke et al, 2018; Maskell, Newcombe, Martin, & Kimble, 2013; Sveen, Sjöberg, & Öster, 2014; Willebrand et al, 2011); 25 studies focused on adults (Abrams, Ogletree, Ratnapradipa, & Neumeister, 2016; Bayuo, Agbenorku, & Amankwa , 2016; Christiaens et al, 2015; Elsherbiny, Salem, El‐Sabbagh, Elhadidy, & Eldeen, 2011; Goyatá & Rossi, 2009; Hunter et al, 2013; Idrees, Faize, & Akhtar, 2017; Jang, Park, Chong, & Sok, 2017; Johnson, Taggart, & Gullick, 2016; Juozapavicien, Rimdlka, & Karbonskiene, 2012; Kornhaber, Wilson, Abu‐Qamar, & McLean, 2014; Liang, Wang, Yao, Pan, & Wang, 2012; Martin, Byrnes, McGarry, Rea, & Wood, 2017; Mashreky et al, 2008; Ohrtman et al, 2018; Park, Choi, Jang, & Oh, 2008; Pfitzer et al, 2016; Shahid, Ismail, & Khan, 2018; Sproul, Malloy, & Abriam‐Yago, 2009; Titscher, Lumenta, Kamolz, Mittlboeck, & Frey, 2010; Wasiak et al, 2014; Wiechman et al, 2018; Yuxiang et al, 2012; Zamanzadeh, Valizadeh, Lotfi, Salehi, & Khalili, 2016; Zhang et al, 2014); and three studies focused on both adults and children with burns (Ahuja, Mulay, & Ahuja, 2016; Simons, Price, Kimble, & Tyack, 2016; Vetrichevvel et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Expressions of guilt and insecurity (Abrams et al, 2016; Zamanzadeh et al, 2016) and feelings of being fed up and ambivalent (Simons et al, 2016) were also noted in the postdischarge period. The presence of scarring is associated with feelings of shame, body dissatisfaction, and the need to conceal (Duke et al, 2018; Hunter et al, 2013). Burns to the hands, face, and neck also evoked more psychological distress among adults (Duke et al, 2018; Titscher et al, 2010; Kornhaber et al, 2014; Zhang et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation